Ekstraksi dan Karakterisasi Gelatin Kulit Ikan Mahi-Mahi (Coryphaena hippurus) dengan Pretreatment Asam Kandis dan Ultrasonikasi - Fhadillah Putri Soti; Syamsi Aini (MASALIQ, 2026)
The utilization of mahi-mahi (Coryphaena hippurus) skin as a raw material for gelatin is an effort to enhance the value of fishery by-products through an extraction method based on natural materials. This study aimed to determine the characteristics of gelatin from mahi-mahi skin produced through pretreatment using kandis acid and extraction with an ultrasonic bath. Gelatin characterization was conducted based on yield, physicochemical parameters, and functional group identification using Fourier Transform Infrared Spectroscopy (FTIR). The results showed that the resulting gelatin had a yield of 13.60%, moisture content of 6.59%, ash content of 1.02%, fat content of 1.80%, pH of 6.98, viscosity of 2.15 cP, melting point of 21 °C, and gel point of 3 °C. FTIR analysis identified the absorption bands of amides A, I, II, and III at wavenumbers of 3282, 1633, 1528, and 1241 cm⁻¹, respectively. These findings indicate that mahi-mahi skin has the potential to be utilized as an alternative source of gelatin with physicochemical characteristics and functional groups that support the development of materials derived from fishery by-products. The use of kandis acid and ultrasonic extraction also has implications for the development of gelatin production methods that utilize natural materials and are more environmentally friendly.